Switching Response to Power Prices: Evidence from German Households - Gerhard Kussel; Manuel Frondel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Empirical evidence on the response of German households to electricity price changes is largely lacking. Using data from Germany's Residential Energy Consumption Survey (GRECS), we fill this void by employing an instrumental variable approach to cope with the endogeneity of the consumers' tariff choice. Exploiting our information on the households' knowledge about power prices, we additionally employ an Endogenous Switching Regression Model to estimate price elasticities for two groups of households: those that are informed about prices and those that are price-ignorant. With elasticity estimates falling between -0.91 and zero, we find residential electricity demand to be quite inelastic. Households with price information are sensitive to price changes while the demand of uninformed household is entirely price inelastic.
Keywords: Q41; D12; C26; 330